The Moment of Transfer of a Share in a Share Capital of a Limited Liability Company in the Order of Hereditary Succession - A. V. Remizova (Vestnik MGIMO-Universiteta, 2012)
This article analyzes established procedure of inheritance of a share in a share capital of a limited liability company, detection of the problem differences between the moment of transfer of a share in a share capital of a limited liability company to the heirs of a deceased participant from the moment of transfer of rights and duties оf a participant to the heirs.